Pakistan - Public Sector Accounting and Auditing : A Comparison to International Standards - World Bank (Washington, DC, 2012)
This assessment of public sector accounting and auditing for Pakistan is generally meant to help implement more effective public financial management through better quality accounting and public audit processes in Pakistan and to provide greater stimulus for more cost-effective outcomes of government spending. More specific objectives are (a) to provide the country's accounting and audit authorities and other interested stakeholders with a common, strongly-founded, knowledge as to where local practices stand against the internationally developed norms of financial reporting and auditing; (b) to assess the prevailing variances; (c) to chart paths for improving the accordance with international standards; and (d) to provide a continuing basis for measuring improvements.